Ethnomathematics Exploration Types of Angles in The Ampel Religious Area for Elementary School Mathematics Learning - Sri Endarwati; Wiryanto; Endah Budi Rahaju (Elementary Teacher Education Program, Majalengka University, 2024)
Mathematics and culture are two things that are difficult to separate. Mathematics is a branch of science that has developed since ancient times and has become part of human life and culture. The relationship between mathematics and culture is called ethnomathematics. This study aims to explore the mathematical concept of various types of angles found in the Ampel Religious Area for mathematics learning in elementary schools. The main focus of this study is the forms of buildings or architecture, ornaments, and objects in the Ampel Mosque and its surroundings. The research location was at the Ampel Mosque and its surroundings located on Jalan Ampel Masjid, Semampir District, Surabaya City, East Java. This study uses an ethnographic approach with a qualitative research type. Data were collected through observation and documentation techniques. There are three data analysis techniques used, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that there are mathematical elements about the types of angles in the area. The types of angles found include acute angles, right angles, obtuse angles, straight angles, reflex angles, and 360° angles. The results of ethnomathematics exploration in the Ampel Religious Area can be used by teachers as a reference for mathematics learning for elementary school students, so that they can learn more about local culture and understand the types of angles. Keywords: ethnomathematics, religion, Ampel, angles